Morningness/eveningness effects on autonomic function during a high intensity interval training protocol in soccer players. A randomized cross-over study - Bonato, M.; Vitale, A.; Mancuso, G.; Merati, G.; La Torre, A. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: The 4x4 min of interval running proposed by Helgerud et al., (2001) is one of the widely used methods that have been demonstrated to improve soccer performance. For this reason, monitoring the effects of this type of training could provide useful information to make evidence based decisions on appropriate loading schemes to enhance team performance and reduce injuries. Therefore, the aim of this study was to assess the acute effects on heart rate variability (HRV) of this training protocol performed at different times of the day (8.00 am vs 8.00 pm). Methods: In a cross-sectional study, 30 male recreational soccer players, age 20±2 y-o, were randomized to morning (MG=15) or evening group (EG=15). Subjects performed an aerobic interval training protocol consisted of four times 4 min at 90-95% of maximal heart rate (assessed during a Yo-Yo IR1 test) with a 3-min jog in between. HRV was measured at REST, PRE, POST-12h and POST-24h the 4x4 protocol. HR variability indexes in time, Root Mean Square of the Successive Differences (RMSSD) and the standard deviation of NN intervals (SDNN), frequency (Low Frequencies, between 0.04 and 0.15 Hz [LF], and High Frequency, between 0.15 and 0.40 Hz [HF], in normalized unit) were calculated. Results: One-way ANOVA showed that both morning/evening aerobic interval training protocol significantly increased the parasympathetic cardiac tone POST-12h (p<0.05) which returns to baseline level POST-24h. Un-paired t-test detected significant difference in PRE aerobic training in LnRMSS (p=0.049), LnSDNN (p=0.043), HF n.u. (p=0.021), showing that in evening conditions subjects have an increased parasympathetic activity. In POST-12h subjects that trained during the evening have an increased LnRMSS (p=0.043), LnSDNN (p=0.032), HF n.u. (p=0.024), maybe due to a reduced recovery. No differences in POST-24h both in sympathetic and parasympathetic activity were detected. Discussion: The 4x4 protocol seems to influence the parasympathetic tone in the same way both in morning and evening conditions. On the other hand, in PRE conditions people that train in the evening showed an increased parasympathetic cardiac tone. Because soccer players have often to train twice a day during the season, with morning and evening training sessions, monitoring HRV is a useful and non-invasive method to detect the effects of high intensity interval training, with the aim to facilitate a more efficient planning and manipulation of training sessions.